As cantigas de romaria galego-portuguesas e suas formosas donzelas: uma maneira de "orar com os pés" e com o coração - Rafael Teixeira de Paula Lima (2011)
This study aims to examine the Galician-Portuguese Cantigas de Amigo in their subgenre Romaria through the guiding lights of the sacred-profane dichotomy and the symptomatology of love. Based on these theoretical and methodological assumptions, this work looks forward to view, point and analyze the intertextual aspects of the subgenre, also highlighting their dissonances in what is patent at the Corpus Medieval Trovadoresco Galego-Português as a whole.